CASPIAN OIL: ITS EXPORT ROUTES AND TRANSPORTATION PROBLEMS - TEVZADZE, Zurab (CENTRAL ASIA AND THE CAUCASUS, 2004)
Gaining access to the world market will place the new oil- and gas-producing states of the Caspian region in intense competition with the Near and Middle East and Russia, the largest oil and gas exporters. The country that can offer reliable delivery of these commodities at the lowest production and transportation costs will come out on top. After all, the problems encountered in this area are having a direct effect on the economic efficiency of oil-producing projects, since developing even low-capacity fields might be highly profitable if they are conveniently located, making it possible to deliver hydrocarbons to the markets at minimal cost. Whereas the economic efficiency of a field is significantly reduced if an ex-pensive transportation infrastructure has to be built to deliver its oil to the consumers. Doing a cost appraisal requires looking at the key factors that influence a decision in favor of a particular route (or several). Here we should keep in mind the total and annual export volume, production costs, particular legislation features and rights in the producing and transit countries, whether the oil’s quality can be preserved during shipment by di-versified routes and with other types of transportation, natural geographic and export limitations, the special features of the transportation infrastructure, supply forecasts, demand prospects, and so on. The author of this article is interested not so much in the prospective oil supplies in the region, the development of which might begin in the future, as in the estimated economic potential of the surveyed fields. This will make it possible to make at least an approximate estimate of how much it will cost to deliver oil to the world market within the framework of the international consortiums actually in operation. In order to do this, we chose four large consortiums created on the basis of production shar-ing agreements (PSA) and already engaged in pro-duction or about to begin it in the next few years (see Table 1). One of them is the Azerbaijan Inter-national Operating Company (AIOC), which is developing the Azeri-Chirag-Gunashli field. And there are three consortiums operating in Kazakhstan: TengizChevrOil (TCO, developing the Tengiz and Korolevskoe fields), the Karachaganak Integrated Organization (KIO, working the Karachaganak field), and the Kazakhstan North-Caspian Operating Company (Agip KCO, developing the Kashagan field).